Readily available concentrations of selected micronutrients and harmful metals in soils of Sub-Saharan Africa - Keskinen, R.; Nyambura, M.; Heikkinen, J.; Sila, Andrew M.; Eurola, M.; Towett, Erick K.; Esala, M. (Elsevier, 2019)
An adequate supply of micronutrients is essential for balanced plant growth. In Africa, micronutrient constraints are known to restrict crop productivity and impair human welfare and health. We analyzed a total of 816 topsoil and 796 subsoil samples from Sub-Saharan Africa, to provide baseline information on their readily available Al, B, Cd, Co, Cr, Cu, Fe, Mn, Mo, Ni, Pb, V, and Zn concentrations. This work builds on previous global micronutrient surveys. The studied soils were low in hot water-extractable B, acid ammonium acetate-EDTA-extractable micronutrients, and potentially harmful metals. In comparison with tentative critical level values, B, Cu, Zn, Mo, and Fe in a considerable number of samples seemed to be at a low level for crop production. Apart from Al, Mo, V, Pb, and Cr, readily available element concentrations were higher in topsoil than subsoil. Concentrations of harmful metals (Cd, Ni, Pb) and of Mn and Mo were enriched in cultivated soils in comparison with semi-natural sites. Among the 11 Reference Soil Groups represented in the study, Arenosols were discernible as poor in Cr, Cu, and Fe. Other significant differences in microelement concentrations between soil groups were found only for Ni and V.